OS SENTIDOS DA LEITURA PARA AS PROFESSORAS DO ENSINO FUNDAMENTAL - Salomé, Liliane Cremonese (2010)
Over the last years, studies on teaching of written language approached the reading practice as a cultural production that which originates from social communication contexts and constitutes as a social inclusion instrument and political participation. These ideas were taken by official speeches and widely spread in educational circles in the State of São Paulo in different programs of continuing education. In this context, this research is based on the theory of social representations developed by Serge Moscovici to look into the purposes attributed to the act of reading and the relevance of this cultural practice in the group of teachers´ life who teach in the first four years of primary education. For the development of thes work, the practices and reading preferences of teachers were taken into account, the history of teaching the reading and the social representations about the practice of reading among women. By means of method of analysis of the content it was possible to develop the representations of reading, present in the teachers´ speech, contributing to the awareness of their ways of receiving the practice of reading.(AU)